Identification and functional analysis of the pre-piRNA 3′ Trimmer in silkworms - Izumi, Natsuko (Cell, 2016)
PIWI-interacting RNAs (piRNAs) play a crucial role in transposon silencing in animal germ cells. In piRNA biogenesis, single-stranded piRNA intermediates are loaded into PIWI-clade proteins and cleaved by Zucchini/MitoPLD, yielding precursor piRNAs (pre-piRNAs). Pre-piRNAs that are longer than the mature piRNA length are then trimmed at their 3′ ends. Although recent studies implicated the Tudor domain protein Papi/Tdrkh in pre-piRNA trimming, the identity of Trimmer and its relationship with Papi/Tdrkh remain unknown. Here, we identified PNLDC1, an uncharacterized 3′–5′ exonuclease, as Trimmer in silkworms. Trimmer is enriched in the mitochondrial fraction and binds to Papi/Tdrkh. Depletion of Trimmer and Papi/Tdrkh additively inhibits trimming, causing accumulation of ~35–40-nt pre-piRNAs that are impaired for target cleavage and prone to degradation. Our results highlight the cooperative action of Trimmer and Papi/Tdrkh in piRNA maturation.